Using Real-Time Integrated Computer Vision and Deep Learning for Advanced Factory Safety - Tsai, Shang-Te; Chang, Yu-Cheng; Huang, Chao-Yi; Yang, Fang-Yuan; Chien, Wei; Wu, Zong-Rong (2024 IEEE 4th International Conference on Electronic Communications, Internet of Things and Big Data (ICEIB), 2024)
Innovative safety in the workplace is vital as the high safety risks associated with electrical engineering construction can lead to injuries or even fatalities. Using computer vision technology, we experimented with scenarios such as "normal operations" and "unexpected incidents" to enhance safety measures. We integrated an Internet of Things system into the setup, enabling the system to quickly detect and alert to unexpected events in real-time, thereby improving workplace safety.